Vozes das masculinidades e sexualidade : narrativas de meninos do ensino médio em uma escola pública de Cuiabá-MT - Costin, Sirlei Cleuza (2024)
The study of gender relations in the school environment has been growing and gaining ground in academic circles, as well as posing a challenging issue in teacher education. In high school, we have young people who begin, modify, or simply explore experiences in all contexts, including sexual ones. This is part of a process of curiosity, confirmation, or denial of knowledge, values, and practices already learned/known and which may not satisfy them in this peculiar phase of adolescence. Thus, this dissertation aims to analyze the narratives of boys regularly enrolled in high school at a public school in Cuiabá-MT, regarding the youth who deepen and diversify gender relations in the school context. Taking into account these factors, this research proposed to investigate the following problem: How do boys, high school students at a public school in Cuiabá – MT, perceive masculinities and sexuality? In terms of methodology, qualitative methodology was used for the analysis of this work, through interviews and group discussions. We noticed that support and debate have mainly come from students, who welcome, discuss, and question in their daily conversations and experiences, without necessarily the school conducting any work or promoting actions on diversity and inclusion, gender violence, homophobia, among others. The investigation also indicates that students recognize gender and sex categories, despite the confusion established between some terms, contributing to the social construction of broader meanings, as they are constructed relationally, through coexistence and encounter among different expressions.